Evaluation of microbial contamination in the inner surface of titanium implants before healing abutment connection: A prospective clinical trial - Lucena, George Alexandre de Barros; de Molon, Rafael Scaf [UNESP]; Moretti, Antonio J.; Shibli, Jamil Awad; Rêgo, Delane Maria (Quintessence Publishing, 2018)
Purpose: The objective of this investigation was to assess the microbiologic contamination in the inner surface of titanium implants prior to prosthetic abutment placement. Materials and Methods: The study population consisted of partially edentulous individuals who had previously received at least one internal hexagon titanium dental implant. A bacterial sample of the inner surface of the individual dental implant was taken after surgical reopening for healing abutment placement. The samples were allocated in order to evaluate three distinctive variables as follows: (1) location (mandible vs maxilla), (2) early exposure of implants to the oral cavity (cover screw) throughout the healing stage (exposed vs not exposed), and (3) existence or lack of keratinized mucosa (KM). The microorganism species detected were examined by checkerboard DNA-DNA hybridization. Results: A total of 32 partially edentulous patients with 78 implants placed in both the maxilla and mandible were enrolled: 8 men and 24 women, ranging in age from 27 to 64 years (mean age: 47.7 years). Bacteria were detected in 20 patients, distributed in 41 implants. Spontaneous early implant exposure and absence of KM did not increase bacterial contamination in the inner surface of implants. A significant increase in the detection of 22 bacterial species was found in the mandible when compared with the maxilla. Conclusion: Microbial biofilm accumulation in the implant's internal surface might happen before healing abutment placement. Exposure of implants to the oral cavity and absence of KM were not directly related to a greater microbial biofilm count. The results suggested that submerged healing does not protect implants against bacterial colonization.
Keywords: Checkerboard DNA-DNA hybridization; Dental implants; Microbiology; Peri-implantitis